PERANCANGAN SISTEM INFORMASI POSYANDU BERBASIS WEBSITE SEBAGAI IMPLEMENTASI E-GOVERNMENT DESA MENGGUNAKAN DESIGN THINKING - Firmani, Eka; Krisbiantoro, Dwi; Wulandari, Oca Meilika (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2026)
Posyandu as a community-based health service still faces problems in data management carried out manually using conventional books, causing data to be prone to loss, unintegrated, and limited access to health information for the community. This condition hinders the effectiveness of health services for toddlers and the elderly at the village level. This study aims to design and develop a website-based Smart Health Village information system as an implementation of e-government at the village level using the Design Thinking approach. The Design Thinking method is applied through five stages, namely Empathize, Define, Ideate, Prototype, and Test, which enables system development based on the actual needs of users. The system development involved three posyandu cadres and six residents as informants. The resulting system has three user roles, namely Admin, Village Apparatus, and Residents, with main features including toddler and elderly data management, health examination recording, posyandu activity scheduling, and reports that can be exported to PDF format. System testing was carried out using the Black Box Testing method with twelve testing scenarios which showed that all functional features of the system ran as expected. With this system, it is hoped that posyandu health services can potentially improve service efficiency digitally, accurately, and sustainably as a concrete manifestation of e-government implementation at the village level.